Numerical Simulation of Turbopump Inducer Cavitating Behavior - Coutier-Delgosha O.; Morel P.; Fortes-Patella R.; Reboud JL. (International Journal of Rotating Machinery)
In the present study a numerical model of 3D cavitating flows is proposed. It is applied to investigate the behavior of a spatial turbopump inducer in noncavitating and cavitating conditions. Experimental and numerical results concerning inducer characteristics and performance breakdown are compared at different flow conditions. The cavitation development and the spatial distribution of vapor structures within the inducer are also analyzed. The results show the ability of the code to simulate the quasi-steady cavitating behavior of such a complex geometry. Discrepancies concerning the breakdown prediction are also discussed.